Men’s Attitudes To Condoms And Female Controlled Means Of Protection Against HIV And STDS In South-Western Uganda - Pool, Robert; Hart, Graham; Green, Gillian; Harrison, Susan; Nyanzi, Stella; Whitworth, Jimmy (Culture, Health & Sexuality, 2000)
There is widespread demand for the development of female controlled methods of protection against sexually transmitted diseases (STDs) and HIV. The success of such methods will not only depend on their acceptability to women but also to their male partners. This paper reports on men's attitudes to female controlled methods in south west Uganda. Data was gathered in individual interviews with 50 men and 7 focus group discussions with 42 men. Male attitudes to the male condom, the female condom and female controlled methods of protection generally were characterized by ambiguity and anxiety. They liked the male condom because it protects against infection and unwanted pregnancy, but were worried by rumours that it was unreliable. The central theme in the discussions was men's anxiety about retaining control over their female partners. The men wanted women to be protected (and therefore safe as potential partners) but they also wanted to remain in control, at least to some extent, of the means of protection. Once suitable female controlled methods have been identified, it will be necessary to use education and social marketing in such a way that men can be reassured of the positive benefits of these products to them, as well as to women.